Enhancing Safety and Reliability of Electric Power Supply to Consumers through Safe Electricity Networks of up to 1 kV - Yurii Shelekh; Myroslav Sabat; Vladyslav Lysiak; Lidija Parashchuk (Energy Engineering and Control Systems, 2021)
The study presents an electric network that allows both increasing the level of electrical safety and eliminating one-phase damage to the electrical network without switching off the consumer's electric energy. The application of the network does not require significant investments. The technical feasibility of implementing an electrical installation with voltage values in the emergency mode on the leading parts, which does not exceed the permissible values for normal mode, is demonstrated. An additional advantage of the proposed technical solution is the immutability of the voltage at the customer's outputs, which allows it to operate normally also in the emergency mode of the electrical installation.